Urban green spaces diversity and their added value to urban sustainability: a case study from Bragança (Portugal) - Gonçalves, Artur (2018)
Urban green spaces (UGS) combine a wide range of elements that offer diverse ecosystem services, such elements are often measured in a single general category without valuing diversity. This study carried out in Bragança (Portugal), a small town with a population of around 25,000 inhabitants, uses spatial metrics (ArcGis 9.3 - ESRI ® - software) to identify and measure characteristics of local UGS, applying a framework for its classification and addressing its attributes, including their ownership, access, vegetation, relation with biophysical context, cultural value and urban planning determinations. Further information, related to the social relation with the UGS was also gathered with questionnaires to 251 inhabitants, addressing a representative sample (proportional to gender and age groups), and taking into account the spatial distribution of the population. The results show that many of the UGS are not developed to ensure an adequate response to social demands (eg. recreational needs) and even offer little interest from the perspectives of urban resiliency and sustainability. Finally, it is argued that UGS should be addressed considering the urban green infrastructure perspective and should be carefully planned to ensure that they have a valuable impact on urban life quality.